Concentration‐QTc Modeling of Ozanimod’s Major Active Metabolites in Adult Healthy Subjects - Briggs, Emily; Chapel, Sunny; Zhang, Peijin; Palmisano, Maria; Tran, Jonathan Q. (CPT: pharmacometrics and systems pharmacology, 2021)
Ozanimod, approved by regulatory agencies in multiple countries for the treatment of adults with relapsing multiple sclerosis, is a sphingosine 1‐phosphate (S1P) receptor modulator, which binds with high affinity selectively to S1P receptor subtypes 1 and 5. The relationships between plasma concentrations of ozanimod and its major active metabolites, CC112273 and CC1084037, and the QTc interval (C‐QTc) from a phase I multiple‐dose study in healthy subjects were analyzed using nonlinear mixed effects modeling. QTc was modeled linearly as the sum of a sex‐related fixed effect, baseline, and concentration‐related random effects that incorporated interindividual and residual variability. Common linear, power, and maximum effect (Emax) functions were assessed for characterizing the relationship of QTc with concentrations. Model goodness‐of‐fit and performance were evaluated by standard diagnostic tools, including a visual predictive check. The placebo‐corrected change from baseline in QTc (ΔΔQTc) was estimated based on the developed C‐QTc model using a nonparametric bootstrapping approach. QTc was better derived using a study‐specific population formula (QTcP). Among the investigated functions, an Emax function most adequately described the relationship of QTcP with concentrations. Separate models for individual analytes characterized the C‐QTcP relationship better than combined analytes models. Attributing QT prolongation independently to CC1084037 or CC112273, the upper bound of the 95% confidence interval of the predicted ΔΔQTcP was ~ 4 msec at the plateau of the Emax curves. Therefore, ΔΔQTcP is predicted to remain below 10 msec at the supratherapeutic concentrations of the major active metabolites.